An experimental and numerical study of the ballistic behavior of an epoxy matrix hybrid composite reinforced with aramid fabric and fique fabric - Bernardo Soares Avila de Cêa; Raí Felipe Pereira Junio; Douglas Santos Silva; Fábio da Costa Garcia Filho; Sergio Neves Monteiro; Lucio Fabio Cassiano Nascimento (Journal of Materials Research and Technology)
Composites for ballistic armor generally use high-performance synthetic fibers due to their excellent properties, but they have a high cost and environmental impact. Natural lignocellulosic fibers emerge as a more sustainable alternative, although they face challenges. Hybrid composites, which combine natural and synthetic fibers, were developed to combine efficiency, cost reduction and lower environmental impact. In this study, an epoxy matrix composite reinforced with synthetic aramid fibers and fique fibers was evaluated. The composites were subjected to ballistics tests to investigate the absorption of kinetic energy. The Weibull probabilistic statistical treatment was used and numerical analyses were compared to the experimental data. The average residual velocity (358.96 m/s) and absorbed energy (224.73 J) data were similar to reference works. The Weibull parameters showed good reliability with the R2 precision adjustment between 0.95 and 0.978. With the ANSYS Material Design module, it was possible to obtain the RVE of the epoxy/fique laminate and its respective properties. Using the ANSYS Composite Prep-Post (ACP) module, it was possible to generate a model of the epoxy/fique/aramid hybrid composite and identify its properties and stiffness and compliance matrices. The results obtained for residual velocity (355 m/s) and absorbed energy (201.5 J), from the numerical analyses, showed an approximation of the experimental results. The Contact Force graph allowed observing all the interaction that occurred between the projectile and the test specimen, with the greatest acting force of 6794.7 N, until the moment in which the interaction between the bodies is considered null.